Efficacy of combined doxycycline and intense pulsed light therapy for the management of intractable recurrent chalazion - Yoon, Hyeon-Jeong; Moon, Ja Young; Yoon, Kyung Chul (Frontiers in Medicine, 2024)
Management of chalazion, characterized by noninfectious chronic granulomatous inflammation of the meibomian glands (MGs), remains challenging in ophthalmic practice, particularly because of its propensity for recurrence even after surgical intervention. This study aimed to evaluate the combined efficacy of doxycycline and intense pulsed light (IPL) therapy for treating intractable recurrent chalazion, focusing on reducing recurrence rates and improving MG status. This retrospective study included patients with intractable recurrent chalazion refractory to conventional treatments including surgical intervention and antibiotics. All patients were treated with a combination of doxycycline and IPL therapy. Clinical assessments included best-corrected visual activity, intraocular pressure, and MG evaluations using slit-lamp biomicroscopy and Keratograph 5M topography. The study included 12 patients (5 male and 7 female) with an average age of 36.3 years. Treatment outcomes were categorized as 'success' (83.3%), 'stationary' (8.3%), and 'failure' (8.3%). Significant improvements were noted in the MG expression scores (p=0.038), MG quality scores (p=0.045), and lid margin telangiectasia scores (p=0.002). In addition, significant improvement in meiboscores was observed (p=0.002). The combination of doxycycline and IPL therapy demonstrated promising efficacy in treating intractable recurrent chalazion, with significant improvements in MG function and reduced recurrence rates. This treatment approach offers a viable alternative for patients with recurrent chalazions, particularly for those who are unresponsive to conventional treatments.